1981
DOI: 10.1136/jech.35.1.71
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and severity of urinary incontinence in women.

Abstract: SUMMARY One thousand and sixty women aged 18 or over, randomly selected from a defined geographical area in South Wales, were interviewed at home about their urinary symptoms. Ninety-five per cent co-operated, of whom 45% admitted to some degree of incontinence. 'Stress' incontinence was reported by 22% of women, 'urge' incontinence by 10%, and both types combined-'complex'-by 14%. In most women urinary loss was both small and infrequent but 5% of all women experienced a loss sufficient to necessitate a chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
98
3
5

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(119 citation statements)
references
References 6 publications
13
98
3
5
Order By: Relevance
“…In other similar study, the reported prevalence was 21.87%. [13][14][15] Prevalence of various types of incontinence in our studies, were similar to the study conducted by Kumari et al, who reported the overall prevalence of UI as 12%, among whom 46% had stress incontinence, 26% had urge, and 28% had mixed type. 14 In another study, the prevalence of stress, mixed, and urge type was 16.13%, 3.67%, and 2.07%, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In other similar study, the reported prevalence was 21.87%. [13][14][15] Prevalence of various types of incontinence in our studies, were similar to the study conducted by Kumari et al, who reported the overall prevalence of UI as 12%, among whom 46% had stress incontinence, 26% had urge, and 28% had mixed type. 14 In another study, the prevalence of stress, mixed, and urge type was 16.13%, 3.67%, and 2.07%, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…According to many studies prevalence of urinary incontinence ranged from 5% to 72% among community-dwelling women [7][8][9]. Our results of urinary incontinence lie in the lower end of the range because in our country urine leak is considered an age related problem and consultation is not sought because of embarrassment.…”
Section: Discussionmentioning
confidence: 74%
“…(6) 27.6% of patients suffered from urinary incontinence (Stress, urge and mixed) According to many studies prevalence of urinary incontinence ranged from 5% to 72% among community dwelling women. (7)(8)(9) our results of urinary incontinence lie in the lower end of the range because in our country urine leak is considered an age related problem and consultation is not sought because of embarrassment, lack of awareness and low education level.…”
Section: Resultsmentioning
confidence: 99%
“…(6) 27.6% of patients suffered from urinary incontinence (Stress, urge and mixed) According to many studies prevalence of urinary incontinence ranged from 5% to 72% among community dwelling women. (7)(8)(9) our results of urinary incontinence lie in the lower end of the range because in our country urine leak is considered an age related problem and consultation is not sought because of embarrassment, lack of awareness and low education level.Urge incontinence was found relatively more common in our study as compared to stress incontinence. Stress incontinence is more common than urge incontinence according to many studies (9,10) this difference is in the structure of society and the psychosocial problems faced by Indian women.…”
mentioning
confidence: 99%